Padrões de coocorrência da assembleia de Copépodes (Crustacea) em distintos ambientes da planície de inundação do alto rio Paraná/PR/MS. - Lopes Filho, Danilo Rezende (2013)
One of the main issues in community ecology is the detection of structure patterns and the factors responsible for them. In this study, null models were used to identify possible co-occurrence patterns in the assemblage of copepods sampled in marginal lakes in the upper Paraná River floodplain, during 2000 and 2010. The lakes differ in the physical and chemical properties of their water relative to the degree of connectivity with the main river channel, influencing the structure of the copepod assemblage in these environments. We selected sixteen connected lakes, permanently connected with the main channel of the river, and thirteen isolated lakes without such connection. The assemblage was divided into copepod feeding guilds, predators and filter feeders, as the analysis of heterogeneous groups regarding the use of resources can dilute ecological processes, leading to stochasticity of the assemblage. The C-score model was chosen to test the null hypothesis of randomness of the copepod assemblage. The null model showed that the assemblage was structured in 2000 and 2010 for the filter feeding copepod guild, without distinction between the degree of connectivity of the environments. The canonical correspondence analysis, performed to show the influence of abiotic factors on the copepod assemblage structure, evidenced reasonable explanatory power in structuring the filter feeding copepod assemblage in the studied environments with no difference between the connectivity degrees.